Diet Rendah Protein Meningkatkan Jumlah Neuron Nitrergik Duodenum dan Jejunum Serta Menurunkan Bobot Badan Tikus Wistar (LOW PROTEIN DIET INCREASES THE NUMBER OF DUODENUM, JEJUNUM NITRERGIC NEURONS AND REDUCES BODY WEIGHT IN THE WISTAR RATS) - Hana, Raden Rara Amelia; Sarmin, Sarmin; Airin, Claude Mona; Astuti, Pudji (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.539, 2019)
Protein is very important for the growth, development and activity in rats. The impact of lack protein intake to gastrointestinal, especially in the small intestine, the number of nitrergic neurons, and changes in body weight in Wistar rats has not been studied. Therefore the aims of this study to examine the effect of a low-protein diet for 4 weeks on the number of duodenal, jejunal, ilealnitrergicneuron and changes in body weight in Wistar rats. Nine male Wistar (Rattusnorvegicus) rats, aged 1 month, with an average body weight of 120 grams used in this study. The rats were adapted for 7 days in individual cages with a normal diet (containing 24% protein) and drinking ad libitum. After being adapted all rats were divided into 3 groups (K-24, K-14, and K-4), consist of 3 rats. Then all rats fasted for 12-hours. Each group received treatment as follows: K-24 group (as a control) was given a diet containing 24% of protein, K-14 group was given a diet containing 14% of protein, and K-4 group was given a diet containing 4% of protein . Diet and drinking water are given ad libitum. Along of treatment for 4 weeks.body weights and blood glucose were measured every weeks, then all rats were euthanized and sample tissues of duodenum, jejunum, and ileum were then were obtained for histopathological preparations using the NADPH-d technique. Data on the number of nitrergicmyenteric neurons in the duodenum, jejunum, and ileum, body weight gain, and blood glucose levels were statistically analyzed by single factor design Anova. The results of this study concluded that a low protein diet (14% and 4% protein) for 4-weeks in the duodenum, jejunum have been increased the number of nitrergic neurons, on the other hand, in the ileum have been decreased the number of nitrergic neurons, reduced body weight, and did not increase blood glucose levels in Wistar rats.